Relational leadership, storytelling, and narratives: practices of local government chief executives - Orr, Kevin; Bennett, Mike (2017)
This article examines the storytelling and narrative practices of an elite group of public administrators in the United Kingdom: local government chief executives. The authors do so through the lens of relationality, exploring the collective dimensions of leadership. The focus on leadership and stories embraces the narrative turn in public administration scholarship. It responds to calls for research examining the distinctive settings of everyday leadership action. The contribution to theory is a qualitative understanding of the relational ways in which stories and narratives are used in the practices of public administration leaders. The article analyzes four ways in which such leadership is accomplished: inviting an emotional connection and commitment to public service, making sense of organizational realities, provoking reflections on practices and assumptions, and managing relations with politicians. The authors offer an appreciation of how relational leadership influence can be generated by expressive narratives and storytelling rather than stemming from bureaucratic authority. - Reproduced.
Keywords: Leadership; Local government